2009
DOI: 10.1007/s12253-009-9156-y
|View full text |Cite
|
Sign up to set email alerts
|

Aminobisphosphonate Stimulates Bone Regeneration and Enforces Consolidation of Titanium Implant into a New Rat Caudal Vertebrae Model

Abstract: Bisphosphonates are widely used as therapeutic agents in bone disorders including cancer metastasis due to their osteoclast inhibitory effect. Recent data shows that bisphosphonates may also induce bone-building by stimulating osteoblast activity. Clinical observations, however, have revealed that bisphosphonates may cause necrosis in the oral cavity which questions their usefulness in bone regeneration during the consolidation of inorganic implants. Here we report the investigation of bone neogenesis followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
(64 reference statements)
0
23
0
3
Order By: Relevance
“…(Original magnification ·4.) [30][31][32] Although the above studies support the beneficial effects of bisphosphonates on new bone formation and implant fixation in both osteoporotic and normal native bones, the potential benefits of bisphosphonates on osseointegration of implants in osteoporotic bone with autogenous bone grafting are less reported. In a previous study by the present authors, 20 it was confirmed that ZA could promote osseointegration and fixation of implants in grafted autogenous bone in osteoporotic rabbits after 3 months of treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(Original magnification ·4.) [30][31][32] Although the above studies support the beneficial effects of bisphosphonates on new bone formation and implant fixation in both osteoporotic and normal native bones, the potential benefits of bisphosphonates on osseointegration of implants in osteoporotic bone with autogenous bone grafting are less reported. In a previous study by the present authors, 20 it was confirmed that ZA could promote osseointegration and fixation of implants in grafted autogenous bone in osteoporotic rabbits after 3 months of treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, a number of studies have demonstrated that bisphosphonates may exert beneficial effects on normal bones as they do on osteoporotic bones. Both new bone formation and implant osseointegration were strengthened by either systemic administration or local immobilization of bisphosphonates in normal animals 30‐32 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ALN does not impair mineralization and seems to preserve or even improve microarchitecture (Owens et al 1997; Rodan 1998; Carbonare et al 2005). The use of bis in joint arthroplasty, which is a current topic of interest, suggests that bis influences the early stages of implant integration positively and may optimize the long‐term survival of the implant (Frenkel et al 2001; Venesmaa et al 2001; Soininvaara et al 2002; Jensen et al 2007; Blazsek et al 2009; Landesberg et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Only one experiment (Chacon et al 2006) has studied the effect of systemic administration of ALN on dental implant osseointegration in non‐osteoporotic rabbits, but the conclusions were based only on torque removal values. The latest research (Blazsek et al 2009) investigating bone neogenesis around an implant inserted into a rat tail vertebra following chronic aminobisphosphonate treatment showed positive results.…”
mentioning
confidence: 99%
“…The X-ray scatter generated on the surface of the samples was subtracted using beam hardening correction algorithm at the level of 60% (Skyscan, Kontic, Belgium). For reconstruction of 3D images we used the cone-beam volumetric algorithm (Feldkamp) 53 . 2| Cut the skin first from the pubis along the sternum and then the wall of abdomen using scissors and forceps, then fix the skin aside by pins.…”
Section: Micro Computer Tomography (Micro-ct)mentioning
confidence: 99%